STUDENTS' ENTREPRENEURSHIP INTENTION AT TEUKU UMAR UNIVERSITY IN AGRO-INDUSTRY SECTOR - Muzammil, Abdul; Aulia, Muhammad Reza; Athaillah, Teuku; Safrika, Safrika; Nasution, Anisah; Atiqah, Qhisthina (Jurnal Bisnis Tani, 2024)
The purpose of this study was to determine the effect of various factors, such as individual characteristics (socio-demography), contextual factors, subjective norm and attitude toward students’ entrepreneurship intention. This study was conducted on 400 students in Teuku Umar University with cluster sampling technique. The sample data were statistically analyzed using Confirmatory Factor Analysis (CFA) and structural Equation Modeling-Partial Least Square (SEM-PLS) with second-order method. The result shows that environment support and attitude was significantly effect on entrepreneurship intention, but education support subjective norm do not show significant effect toward entrepreneurship intention. Many entrepreneurs do not have a high level of education, so everyone has the opportunity to start a business. In addition, a person's intention to start a business starts from himself, if there is no intention from himself, the intention to start a business will be very difficult to realize.